Annual direct medical cost of active systemic lupus erythematosus in five European countries. Issue 1 (21st December 2012) - Doria, Andrea; Amoura, Zahir; Cervera, Ricard; Khamastha, Munther A; Schneider, Matthias; Richter, Jutta; Guillemin, Francis; Kobelt, Gisela; Maurel, Frédérique; Garofano, Anna; Perna, Alessandra; Murray, Miranda; et al.
Abstract : Objectives: To evaluate the annual direct medical cost of managing adult systemic lupus erythematosus (SLE) patients with active autoantibody positive disease in Europe. Methods: A 2-year, retrospective, multicentre, observational study was conducted in five countries (France, Germany, Italy, Spain and the UK). Data included patients' characteristics, disease activity and severity, flare assessments and health resource use (eg, laboratory tests, medications, specialist visits and hospitalisations). Costs were assessed from the public payers' perspective. Cost predictors were estimated by multivariate regression models. Results: Thirty-one centres enrolled 427 consecutive eligible patients stratified equally by disease severity. At baseline, mean (SD) age was 44.5 (13.8) years, 90.5% were women and mean (SD) SLE duration was 10.7 (8.0) years. The SELENA-SLEDAI (11.2 vs 5.3) and SLICC/ACR index (1.0 vs 0.7) scores were higher in severe patients. Over the study period, patients experienced on average 1.02 (0.71) flares/year. The mean annual direct medical cost was higher in severe compared to non-severe patients (€4748 vs €2650, p<0.001). Medication costs were €2518 in severe versus €1251 in non-severe patients (p<0.001). Medications represented 53% and 47% of the total cost for severe and non-severe patients, respectively, primarily due to immunosuppressants and biologics. Flares, especially severe flares, were identified as the major cost predictor, with each flare increasing the annual total cost by about €1002 (p<0.001). Conclusions: The annual direct medical cost of SLE patients in Europe is related to disease severity and flares. Medical treatments were the main cost drivers. Severe flares and major organ involvement were identified as important cost predictors.